The consideration of waste management in environmental impact assessment (EIA) for developments in protected areas. Issue 4 (4th July 2022) - Claassens, C.E.; Cilliers, D.P.; Retief, F.P.; Roos, C.; Alberts, R.C.
ABSTRACT: Waste management is an important consideration for developments within protected areas (PAs). With the growing demand for mainly tourism-related infrastructure in PAs, more urgent and innovate ways of dealing with waste management are required. Internationally environmental impact assessment (EIA) is considered a key policy instrument to inform waste management-related decision-making for new developments. The EIA process makes provision for the identification of waste-related impacts and mitigation measures during the construction-, operation- and decommissioning phases of a development. However, there has been scant reflection on the role of EIA in dealing with waste management decision-making in PAs. Therefore, this research aims to review the extent to which waste management measures are considered in EIAs for developments in PAs. The results show that waste management measures are, for the most part, poorly considered. For example, EIAs failed to provide estimates of expected waste types and quantities and mostly failed to consider the waste management hierarchy. Recommendations are made towards improving the consideration of waste management measures in EIAs for developments within PAs. These include the drafting of guidelines for waste management in protected areas; training relevant roleplayers on waste management measures; and promoting specialist input on waste-related matters for EIAs in PAs.